2001
DOI: 10.1128/mcb.21.14.4441-4452.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of MafA Is Essential for Its Transcriptional and Biological Properties

Abstract: We previously described the identification of quail MafA, a novel transcription factor of the Maf bZIP (basic region leucine zipper) family, expressed in the differentiating neuroretina (NR). In the present study, we provide the first evidence that MafA is phosphorylated and that its biological properties strongly rely upon phosphorylation of serines 14 and 65, two residues located in the transcriptional activating domain within a consensus for phosphorylation by mitogen-activated protein kinases and which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
99
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 68 publications
13
99
1
2
Order By: Relevance
“…5B). The observed mobilities are comparable to those described for the analogous L-Maf mutants where proteins harboring the S65A mutation showed faster mobility than either wild type or those containing the S14A alteration (Benkhelifa et al, 2001) and are independent of the phosphorylation status of the protein.…”
Section: Putative Phosphorylation Sites Of C-maf Are Differentially Usupporting
confidence: 79%
See 1 more Smart Citation
“…5B). The observed mobilities are comparable to those described for the analogous L-Maf mutants where proteins harboring the S65A mutation showed faster mobility than either wild type or those containing the S14A alteration (Benkhelifa et al, 2001) and are independent of the phosphorylation status of the protein.…”
Section: Putative Phosphorylation Sites Of C-maf Are Differentially Usupporting
confidence: 79%
“…We find that alteration of the Ser 15 and Ser 70 residues increases c-Maf activity on the CD13 promoter in the HepG2 liver cell line and thus are inhibitory. However others have found that the S14A/S65A double mutant of L-Maf significantly reduced L-Maf activity (Ochi et al, 2003,Benkhelifa et al, 2001. The mechanisms regulating activation of Maf family proteins have been investigated (Gardner and Montminy, 2005) and include a model invoking bFGF/MEK/ERK-induced phosphorylation that triggers proteosome-dependent degradation (Ochi et al, 2003) to explain L-Maf's decreased stability in neural retinal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study overproduction of MEKK1 did not decrease the amount of MafA produced in JEG cells (data not shown), arguing against a MEKK1-induced degradation of MafA. In addition to protein synthesis or degradation, the transcriptional activity of MafA is regulated by phosphorylation [46]. The present study suggests that IL-1β through activation of MEKK1 phosphorylates MafA or an associated protein, thereby resulting in a decrease of human insulin gene transcription.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, MafA transcriptional activity is regulated by MEKK1 and by IL-1β. MafA belongs to the class of basic region/leucine zipper transcription factors and has been implicated in the development and differentiation of the lens [46]. Moreover, identification of MafA as the transcription factor binding to the C1 element within the rat Ins2 and the INS promoter [16,17] fuelled studies on the role of MafA in beta cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been published that chicken L-Maf, which is the homologue of mouse MafA, is phosphorylated by FGF/ERK signaling pathways and that phosphorylation of L-Maf induces its degradation [52]. In addition, it has been reported that quail MafA is phosphorylated and its phosphorylation is important for maximum transactivation [53]. These data suggest that mouse MafA must also be phosphorylated and that its phosphorylation may regulate the transcriptional activity and/or stability of MafA by extracellular signaling, glucose.…”
Section: Discussionmentioning
confidence: 99%